已知[img=31x25]1803d439f86d190.png[/img]的拉氏变换为[img=124x43]1803d43a00b2dea.png[/img], 求[img=31x25]1803d439f86d190.png[/img]的Z变换。()
A: [img=180x40]1803d43a114ffd8.png[/img]
B: [img=184x51]1803d43a1afcd66.png[/img]
C: [img=186x51]1803d43a25f0be3.png[/img]
D: [img=178x40]1803d43a2ee8b95.png[/img]
A: [img=180x40]1803d43a114ffd8.png[/img]
B: [img=184x51]1803d43a1afcd66.png[/img]
C: [img=186x51]1803d43a25f0be3.png[/img]
D: [img=178x40]1803d43a2ee8b95.png[/img]
举一反三
- 已知[img=31x25]18035f7c4e0b1aa.png[/img]的拉氏变换为[img=124x43]18035f7c563ccdd.png[/img], 求[img=31x25]18035f7c4e0b1aa.png[/img]的Z变换。() A: [img=180x40]18035f7c675fa61.png[/img] B: [img=184x51]18035f7c7227e0d.png[/img] C: [img=186x51]18035f7c7daf415.png[/img] D: [img=178x40]18035f7c860b7b3.png[/img]
- 已知[img=31x25]1802fca0c54e48e.png[/img]的拉氏变换为[img=124x43]1802fca0ce73829.png[/img], 求[img=31x25]1802fca0c54e48e.png[/img]的Z变换。() A: [img=180x40]1802fca0df63e39.png[/img] B: [img=184x51]1802fca0eb34153.png[/img] C: [img=186x51]1802fca0f6ab1fb.png[/img] D: [img=178x40]1802fca0ff6f5c5.png[/img]
- 已知[img=31x25]18031d9d648b582.png[/img]的拉氏变换为[img=124x43]18031d9d6c13756.png[/img], 求[img=31x25]18031d9d648b582.png[/img]的Z变换。() A: [img=180x40]18031d9d7d94e2d.png[/img] B: [img=184x51]18031d9d883a5ca.png[/img] C: [img=186x51]18031d9d9453f28.png[/img] D: [img=178x40]18031d9d9d14397.png[/img]
- 已知[img=31x25]18034a5f85455d7.png[/img]的拉氏变换为[img=124x43]18034a5f8dda3eb.png[/img], 求[img=31x25]18034a5f85455d7.png[/img]的Z变换。() A: [img=180x40]18034a5f9eb8fd1.png[/img] B: [img=184x51]18034a5faa28238.png[/img] C: [img=186x51]18034a5fb55f372.png[/img] D: [img=178x40]18034a5fbee5635.png[/img]
- 在下列命题中:如果f(x)=[img=28x44]17e0bf9914bb2f1.png[/img],那么[img=27x29]17e0bf97582597b.png[/img]f(x)=0;如果f(x)=[img=28x44]17e0bf992111a1c.png[/img],那么[img=27x29]17e0bf97582597b.png[/img]f(x)=0;如果f(x)=[img=55x44]17e0bf992d8de0a.png[/img],那么[img=29x29]17e0bf9939482bb.png[/img]f(x)不存在;如果f(x)=[img=87x53]17e0bf99450fa82.png[/img],那么[img=27x29]17e0bf97582597b.png[/img]f(x)=0。其中错误命题的个数是( A: 0 B: 1 C: 2 D: 3